Prevalence of depression among type 2 diabetes mellitus patients in India: A meta-analysis. (December 2018) - Hussain, Salman; Habib, Anwar; Singh, Ambrish; Akhtar, Mohd; Najmi, Abul Kalam
Highlights: High prevalence of depression was found in Indian T2DM patients. T2DM patients with co-morbid depression have higher odds of developing complications. The diabetes management programs in India may consider early screening of depression. Abstract: Depression as a co-morbid condition in type 2 diabetes mellitus (T2DM) patients is associated with significant morbidity, mortality, and rising health economic burden. Indian healthcare system is heavily burdened with T2DM, and it is important to understand the prevalence of depression associated with T2DM. This meta-analysis conducted as per the registered protocol (PROSPERO registration: CRD42016051552), searched for published studies in the databases including MEDLINE and Embase till 31st August 2018. The modified Newcastle-Ottawa Scale was used to assess the methodological quality. The pooled prevalence of depression among T2DM patients was estimated as primary outcomes, while prevalence based on demographic sub-group was estimated as the secondary outcome. In total, 43 studies including 10, 270 patients fulfilled the eligibility criteria and were included in the analysis. The pooled prevalence of depression in T2DM patients was found to be 38% (95% CI: 31%–45%). Presence of depression in people with type 2 diabetes was more often associated with the presence of complications with an odds ratio of 2.33, 95% CI: 1.62–3.36, p < 0.00001. Overall, the study found a high prevalence of depression among T2DM patients in India. Diabetes management programs in India may consider early screening of depression in T2DM patients.